2016
DOI: 10.1042/cs20160221
|View full text |Cite
|
Sign up to set email alerts
|

The importance of gene–environment interactions in human obesity

Abstract: The worldwide obesity epidemic has been mainly attributed to lifestyle changes. However, who becomes obese in an obesity-prone environment is largely determined by genetic factors. In the last 20 years, important progress has been made in the elucidation of the genetic architecture of obesity. In parallel with successful gene identifications, the number of gene-environment interaction (GEI) studies has grown rapidly. This paper reviews the growing body of evidence supporting gene-environment interactions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 351 publications
(378 reference statements)
2
112
0
2
Order By: Relevance
“…However, the results of the free-choice diet experiments demonstrate an intriguing effect of baseline food preferences on the ability of amylin to suppress intake of particular foods. With the growing interest in individualized medicine for obesity and related comorbidities (Camilleri and Acosta, 2016; Kaul and Ali, 2016; Reddon et al, 2016), these results also underscore the importance of recognizing preexisting individual differences when identifying novel treatment strategies for obesity.…”
Section: Discussionmentioning
confidence: 97%
“…However, the results of the free-choice diet experiments demonstrate an intriguing effect of baseline food preferences on the ability of amylin to suppress intake of particular foods. With the growing interest in individualized medicine for obesity and related comorbidities (Camilleri and Acosta, 2016; Kaul and Ali, 2016; Reddon et al, 2016), these results also underscore the importance of recognizing preexisting individual differences when identifying novel treatment strategies for obesity.…”
Section: Discussionmentioning
confidence: 97%
“…Interaction between PA and Susceptibility Genes Interestingly, while T2DM risk variants do not interact with PA [23], obesity risk variants do [24]. Many studies demonstrated that PA can attenuate in part the impact of obesity-predisposing gene variants like FTO on BMI or body adiposity index in children, adolescents, and adults [25][26][27], which revealed the positive effects of PA on high genetic risk subgroups against obesity.…”
Section: Doi: 101159/000500110mentioning
confidence: 99%
“…Apart from these treatments that act to inhibit the intake of energy, promoting energy expenditure is another approach for the treatment of obesity and associated diseases (Lebrasseur, ; Wang et al , ; Bi et al , ; Pyrzak et al , ). For example, various interventions to increase energy expenditure such as exercise are generally beneficial for the treatment of these metabolic disorders (Jeremic et al , ; Reddon et al , ). In a search for novel pharmacological agents that act by this mechanism, we have recently identified a small molecule bouchardatine (Bou, MW: 289.3) that displays a potent efficacy in decreasing lipid accumulation in 3T3‐L1 adipocytes (Rao et al , ,b).…”
Section: Introductionmentioning
confidence: 99%